High‐Frequency Continuous Monitoring to Track Vapor Intrusion Resulting From Naturally Occurring Pressure Dynamics. Issue 2 (March 2017) - Hosangadi, Vitthal; Shaver, Brandon; Hartman, Blayne; Pound, Michael; Kram, Mark L.; Frescura, Cliff
Abstract : Vapor intrusion characterization efforts can be challenging due to complexities associated with background indoor air constituents, preferential subsurface migration pathways, and response time and representativeness limitations associated with conventional low‐frequency monitoring methods. For sites experiencing trichloroethylene (TCE) vapor intrusion, the potential for acute risks poses additional challenges, as the need for rapid response to exposure exceedances becomes critical in order to minimize health risks and associated liabilities. Continuous monitoring platforms have been deployed to monitor indoor and subsurface concentrations of key volatile constituents, atmospheric pressure, and pressure differential conditions that can result in advective transport. These systems can be comprised of multiplexed laboratory‐grade analytical components integrated with telemetry and geographical information systems for automatically generating time‐stamped renderings of observations and time‐weighted averages through a cloud‐based data management platform. Integrated automatic alerting and responses can also be engaged within one minute of risk exceedance detection. The objectives at a site selected for testing included continuous monitoring of vapor concentrations and related surface and subsurface physical parameters to understand exposure risks over space and time and to evaluate potential mechanisms controlling risk dynamics which could then be used to design a long‐term risk reduction strategy. High‐frequency data collection, processing, and automated visualization efforts have resulted in greater understanding of natural processes such as dynamic contaminant vapor intrusion risk conditions potentially influenced by localized barometric pumping induced by temperature changes. For the selected site, temporal correlation was observed between dynamic indoor TCE vapor concentration, barometric pressure, and pressure differential. This correlation was observed with a predictable daily frequency even for very slight diurnal changes in barometric pressure and associated pressure differentials measured between subslab and indoor regimes and suggests that advective vapor transport and intrusion can result in elevated indoor TCE concentrations well above risk levels even with low‐to‐modest pressure differentials. This indicates that vapor intrusion can occur in response to diurnal pressure dynamics in coastal regions and suggests that similar natural phenomenon may control vapor intrusion dynamics in other regions, exhibiting similar pressure, geochemical, hydrogeologic, and climatic conditions. While dynamic indoor TCE concentrations have been observed in this coastal environment, questions remain regarding whether this hydrogeologic and climatic setting represent a special case, and how best to determine when continuous monitoring should be required to most appropriately minimize exposure durations as early as possible. ©2017 Wiley Periodicals, Inc.